Model Struktural Hubungan Antara Kepercayaan Epistemologis Dengan Konsepsi Tentang Belajar Dan Mengajar Mahasiswa - M. Nur Ghufron; Indiyati Eko P; Berliana Henu Cahyani (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2017)
This research aimed to assessing whether epistemological beliefs as measured by belief about knowledge and belief about learning predicted of the constructivist conception of teaching and learning, assessing whether epistemological beliefs as measured by belief about knowledge and belief about learning predicted of the traditional conception of teaching and learning. The population in this research consists of students of Tarbiyah Department of STAIN Kudus, Central Java. The sample was as many as study 242 students, taken through simple random sampling method. The data collection techniques used in this research was questionnaire in the form of scales and checklists. The data were analyzed using Structural Equation Models (SEM). The research resulted that epistemological beliefs as measured by belief about learning was negatively related on the constructivist conception of teaching and learning and) epistemological beliefs as measured by belief about knowledge was positively related on the traditional conception of teaching and learning.